2016
DOI: 10.1080/02726351.2016.1153545
|View full text |Cite
|
Sign up to set email alerts
|

Study of cut point density and process performance of Floatex density separator in fine coal cleaning

Abstract: Advanced gravity separation of a high-ash (36%) semi-coking coal in a Floatex density separator (FDS) is investigated. The influence of the operating variables on the separation features has been identified. It is established that a higher bed pressure and a higher teeter water flow rate enhance the mass yield of the clean coal albeit with a poorer grade. A higher bed pressure reduces the bed voidage leading to a higher cut point density. Although bed voidage is reduced due to higher teeter water rate, the hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Solid particles in the feed slurry settle down under the gravitational field against the rising current of water. The heavy gangue particles settle down to form a bed while lighter coals are carried to the overflow stream [ 155 , 156 ]. In coal cleaning, FDS is used as a pre-concentrator and/or a classifier prior to other separation processes.…”
Section: Conventional Gravity Separation For Coal Cleaningmentioning
confidence: 99%
See 1 more Smart Citation
“…Solid particles in the feed slurry settle down under the gravitational field against the rising current of water. The heavy gangue particles settle down to form a bed while lighter coals are carried to the overflow stream [ 155 , 156 ]. In coal cleaning, FDS is used as a pre-concentrator and/or a classifier prior to other separation processes.…”
Section: Conventional Gravity Separation For Coal Cleaningmentioning
confidence: 99%
“…In coal cleaning, FDS is used as a pre-concentrator and/or a classifier prior to other separation processes. Teeter water flowrate, bed pressure, set-point, feed rate, and pulp density are the important parameters affecting separation [ 155 , 156 ]. It was also found that higher bed pressure and higher teeter water flowrate could enhance the yield of clean coal albeit with poorer grade [ 156 ].…”
Section: Conventional Gravity Separation For Coal Cleaningmentioning
confidence: 99%
“…The different types of hydraulic classifiers are presented in the work of Tripathy et al [4] and the one studied here is the floatex density separator. Hc units have been the subject of several studies and publications (Bazin et al 2011(Bazin et al -2012, Das et al 2007Das et al -2010; Sar et al 2017 [11]; Sadeghi and Bazin 2020 [12], among others). Generally, the prevailing separation mechanisms in an Hc are hindered settling, elutriation and fluidization [4,13].…”
Section: Introductionmentioning
confidence: 99%